Capital budgeting techniques in a recessionary South Africa - Stern, Gregory Jason (My University, 2014)
ii ABSTRACT The purpose of this research was to examine the decision making process individuals and organisations make with regards to utilising capital budgeting techniques used and the impact operating during a recession or times of uncertainty have on the preference among the techniques. The literature review presents an examination of the existing studies and literature surrounding the most commonly used techniques namely those found within the Discounted Cash Flow and Payback Criteria classification of techniques available. 13 in depth interviews were held with professionals who utilise the techniques to assist their individual organisations to make more sound decisions when looking to invest their money in a capital project. The report presents the results from the interviews while focusing on the techniques used to when evaluating potential investments during times of growth. Then the research examined the impact a recession or times of uncertainty have on the decision making process while examining the critical factors affecting both periods. The research found that although, as per the literature review, the Internal Rate of Return is the preferred technique, there was a difference in the use of supportive techniques when operating in times of growth and those of decline.
MBA Thesis 2014
Keywords: Capital investments, Capital budget